Efficacy and safety of the SQ‐standardized grass allergy immunotherapy tablet in mono‐ and polysensitized subjects. Issue 2 (4th December 2012) - Nelson, H.; Blaiss, M.; Nolte, H.; Würtz, S. Ø.; Andersen, J. S.; Durham, S. R.
Abstract The efficacy of single‐allergen‐specific immunotherapy in polysensitized subjects is a matter of debate. We therefore performed a post hoc analysis of pooled data from six randomized, double‐blind, placebo‐controlled trials (N = 1871) comparing the efficacy and safety of the SQ‐standardized grass allergy immunotherapy tablet (AIT), Grazax (Phleum pratense 75 000 SQ‐T/2800 BAU, ALK, Denmark), in mono‐ and polysensitized subjects. A statistically significant reduction in the mean total combined symptom/medication score (TCS) of 27% was demonstrated in actively treated subjects compared with placebo (P < 0.0001). This was not dependent on sensitization status (P = 0.5772), suggesting a similar treatment effect in mono‐ and polysensitized subjects (i.e. reductions of the TCSs of 28% and 26%, respectively, both P < 0.0001). Finally, a comparable and favourable safety profile of grass AIT was demonstrated in the two subgroups. Thus, no difference in efficacy and safety of single‐allergen grass AIT was observed between mono‐ and polysensitized subjects.